Kekerasan Simbolik dalam Cerita Anak: Analisis Isi pada Majalah Bobo: Symbolic Violence in Children’s Stories: Content Analysis in Bobo Magazine - Rahma Isnania; Nanang Martono; Tri Rini Widyastuti (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2020)
The upper-class dominates various social spaces in society, including children’s stories. Children’s stories as a means of socializing values also participate in socializing upper-class habitus in the storyline. This study aims to describe the children’s habitus as narrated in short stories published in Bobo magazine. The method used in this study is the quantitative content analysis method and critical discourse analysis. This study’s object is about 174 short stories published in Bobo magazine from January 2019 to August 2020, of which 110 stories were taken randomly as samples. The results show that most of the children’s habitus narrated in the stories were upper-class children’s habitus, reaching out to 87 or 79.1% of all stories. Meanwhile, lower-class children’s habitus was found in 30.9% of all stories. The habitus of upper-class children featured in the story consisting of go on an excursion, luxury living, own electronic goods, own expensive good, wearing nightgowns, reading, and writing. On the other side, the habitus of lower-class children habitus featured in the story consisting of playing traditional games, living in poverty, and doing lower-class work. In conclusion, the upper-class children’s habitus appears more dominantly within short stories in Bobo magazine. This study’s results are expected as recommend to parties related to children’s stories publication to present more balanced stories.